2017
DOI: 10.1080/16546628.2017.1344521
|View full text |Cite
|
Sign up to set email alerts
|

Research progress on theaflavins: efficacy, formation, and preparation

Abstract: Background: Theaflavins (TFs) are a category of natural compounds characterized with the benzotropolone skeleton. The prominent benefits of TFs have been well documented. Amount of research were conducted and excellent achievements were disclosed during the past years. However, as far as we know, there is no comprehensive review about TFs.Scope and approach: This review summarized the recent research progress. The activity of TFs on anti-oxidation, anti-mutagenicity, hypolipidemic, anti-inflammatory, anti-canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
62
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(69 citation statements)
references
References 79 publications
0
62
0
1
Order By: Relevance
“…Theaflavin (TF), first found by Roberts et al 17 from black tea, has been demonstrated as having various biological functions, such as radical scavenging, antimutagenicity, hypolipidemic, anticancers, antiviral, as well as anti-inflammatory activity. 18 Kim et al 19 demonstrated that TFs significantly reduced the mRNA level of the lipopolysaccharide (LPS)-induced IL-6, monocyte chemoattractant protein-1, and intercellular adhesion molecule-1 in bone marrow-derived macrophages, inhibited the cytosolic IκBα protein degradation, and blocked the nuclear translocation of RelA (NF-κβ-p65), suggesting that inhibition of pro-inflammatory mediator production by TFs occurred via blocking of NF-κβ signaling pathway. Ukil et al 20 also found that pretreatment with TF- 3,3′-digallate markedly inhibited trinitrobenzene sulfonic acid (TNBS)-induced increases in nuclear localization of NF-κβ, cytosolic IkappaB kinase activity, and preserved IκBα in colon tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Theaflavin (TF), first found by Roberts et al 17 from black tea, has been demonstrated as having various biological functions, such as radical scavenging, antimutagenicity, hypolipidemic, anticancers, antiviral, as well as anti-inflammatory activity. 18 Kim et al 19 demonstrated that TFs significantly reduced the mRNA level of the lipopolysaccharide (LPS)-induced IL-6, monocyte chemoattractant protein-1, and intercellular adhesion molecule-1 in bone marrow-derived macrophages, inhibited the cytosolic IκBα protein degradation, and blocked the nuclear translocation of RelA (NF-κβ-p65), suggesting that inhibition of pro-inflammatory mediator production by TFs occurred via blocking of NF-κβ signaling pathway. Ukil et al 20 also found that pretreatment with TF- 3,3′-digallate markedly inhibited trinitrobenzene sulfonic acid (TNBS)-induced increases in nuclear localization of NF-κβ, cytosolic IkappaB kinase activity, and preserved IκBα in colon tissue.…”
Section: Introductionmentioning
confidence: 99%
“…TFs include TF1, TF2a, TF2b, and TF3 ( Figure 1 ). It is known that TFs account for 2–6% in the dry weight of solids in brewed black tea approximately [ 4 ].…”
Section: Biosynthetic Pathway Of Tfsmentioning
confidence: 99%
“…TFs possess a benzotropolone skeleton. These compounds are produced from their parent catechins ( Figure 2 ) [epicatechin (EC), ECG, epigallocatechin (EGC), and EGCG] by polyphenol oxidase (PPO) or peroxidase (POD) in fresh green tea leaves during the production of black tea leaves or green tea fermentation [ 1 , 2 , 3 , 4 ].…”
Section: Biosynthetic Pathway Of Tfsmentioning
confidence: 99%
See 1 more Smart Citation
“…Theaflavines are considered to be the major bioactives. Four different isoforms such as theaflavin (TF-1), theaflavin-3-O-gallate (TF-2a), theaflavin-3′-O-gallate (TF-2b) and theaflavin-3,3′-O-O-digallate (TF-3) have been described with strong anti-oxidative and anti-inflammatory effects (de Mejia et al, 2009;Gosslau et al, 2018;He, 2017;Ho et al, 2008;Khan and Mukhtar, 2007;Li et al, 2013;Sang et al, 2011;Sharma and Rao, 2009;Yang et al, 2009). Previously, significant anti-inflammatory effects of our theaflavin-enriched black tea extract (BTE) in cell-based, animal, and clinical settings had been demonstrated (Arent et al, 2010;Gosslau et al, 2011;Gosslau et al, 2008).…”
Section: Introductionmentioning
confidence: 99%